2020
DOI: 10.4314/bcse.v34i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Algerian grape juice and their effects on the juice quality

Abstract: The aim of this study was to find a good clarification method to eliminate the substances in Algerian grape juice and study the effects of the clarification agents on juice quality. The clarified grape juice was subjected to different treatments, namely bentonite, gelatin, combination of gelatin and bentonite, then stored for 4 weeks. The effects of fining treatment by determining the critical micillary concentration of each agent used accelerated stability test on turbidity, tannin contents (ethanol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, there is increasing need to provide a scientific basis for the traditional use of different plants and plant parts. For this reason, this study aimed to provide in-depth information on the extraction of essential oil, methanolic extract, biological activities, and mineral compositions of Mentha pulegium L. It is part of an overall program in our laboratory for studying natural food samples relevant to human health and nutrition [ 16 , 17 , 18 , 19 , 20 , 21 ]. The results of this study will be useful in enriching the database of Algerian medicinal herbs, advancing the knowledge on medicinal plants, and deepening the scientific understanding of the medicinal, elemental, and bioactive compounds and antimicrobial properties of Mentha pulegium .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing need to provide a scientific basis for the traditional use of different plants and plant parts. For this reason, this study aimed to provide in-depth information on the extraction of essential oil, methanolic extract, biological activities, and mineral compositions of Mentha pulegium L. It is part of an overall program in our laboratory for studying natural food samples relevant to human health and nutrition [ 16 , 17 , 18 , 19 , 20 , 21 ]. The results of this study will be useful in enriching the database of Algerian medicinal herbs, advancing the knowledge on medicinal plants, and deepening the scientific understanding of the medicinal, elemental, and bioactive compounds and antimicrobial properties of Mentha pulegium .…”
Section: Introductionmentioning
confidence: 99%
“…The clarifying efficiency of gelatin, bentonite, and their mixture on grape juice was investigated by Mazrou et al. (2020). They found that utilization of fining agents in combination form could successfully reduce the turbidity of fresh grape juice from 152 to 6.5 NTU in clarified type.…”
Section: Natural Clarifying Agentsmentioning
confidence: 99%
“…The results showed that Ca-alginate-AC beads can be introduced as an effective adsorbent for removal of patulin from contaminated apple juice. The clarifying efficiency of gelatin, bentonite, and their mixture on grape juice was investigated by Mazrou et al (2020). They found that utilization of fining agents in combination form could successfully reduce the turbidity of fresh grape juice from 152 to 6.5 NTU in clarified type.…”
Section: Combination Of Clarifying Agentsmentioning
confidence: 99%
“…Phenolic compounds are the most abundant compounds followed by sugars and acids ( 41 ). They play a major role in prevention of various diseases caused by oxidative stress ( 50 ). The phenolic compounds found in grape juice are those extracted from grape skins and seeds ( 42 ).…”
Section: Contribution Of Grape Juice To Isotonic Drinksmentioning
confidence: 99%
“…The interest of consumers and the food industry in polyphenols has been growing, because there is a relationship between their intake and prevention of various diseases ( 50 , 54 ). Accordingly biological activities of polyphenols in grape juice are linked to their antioxidant, anti-inflammation, anticancer, anti-aging, antimicrobial, and cardioprotective properties ( 58 ).…”
Section: Contribution Of Grape Juice To Isotonic Drinksmentioning
confidence: 99%